Louis H. Sullivan: that Object He Became - Dan Snyder (Footprint)
Louis H. Sullivan constructed a world view based on a hierarchy of powers. Over this hierarchy he placed the emotion of sympathy. Characterising it as another power he described sympathy as a way of being in communion with the world that manifests in a fusion of identities. Through a close reading of his writings with particular attention paid to his often-encrypted references to Walt Whitman, together with a close reading of selected sources from his library, this essay interrogates his understanding. Sensitive to the question of ‘queering’, it focuses on his conception of fused identities and its effects on gender and sexuality. It excavates an understanding that suggests that Sullivan deliberately constructed an alternative epistemology that overcame a whole host of bipolar oppositions to include male and female. He opted instead for an emotive and fluid ontology where the fixed category of being dissolves in vital consubstantiation – and it was eroticised. Suggesting a uniquely queer stance, Sullivan insists that without a clear vision of it, one may never understand architecture.